Comparison of high dose inhaled steroids, low dose inhaled steroids plus low dose theophylline, and low dose inhaled steroids alone in chronic asthma in general practice. Issue 10 (1st October 2000) - Lim, Sam; Jatakanon, Anon; Gordon, David; Macdonald, Christopher; Chung, Kian Fan; Barnes, Peter J
Abstract : BACKGROUND: Theophylline is widely used in the treatment of asthma, and there is evidence that theophylline has anti-inflammatory or immunomodulatory effects. A study was undertaken to determine whether theophylline added to low dose inhaled steroids would be as efficacious as high dose inhaled steroids in asthma. METHODS: In a study in general practice of 155 recruited asthmatic patients with continuing symptomatic asthma while on 400 μg beclomethasone dipropionate (BDP) daily and inhaled β2 agonist as required, the effect of (1) continuing low dose inhaled steroids alone (LDS, 200 μg BDP twice daily), (2) low dose inhaled steroids plus low dose theophylline (LDT, 400 mg daily), or (3) high dose inhaled steroids (HDS, 500 μg BDP) over a six month period was examined. RESULTS: One hundred and thirty patients completed the study. Between group comparison using analysis of variance showed no overall differences in peak flow measurements, diurnal variation, and symptom scores. Changes in evening peak flows approached significance at the 5% level (p=0.077). The mean improvement in evening peak flow in the LDT compared with the LDS group was 20.6 l/min (95% confidence interval (CI) –2.5 to 38.8). In the LDT group there was an increase in evening peak flows at the end of the study compared with entry values (22.5 l/min), while in the LDS and HDS groups evening peak flows increased by 1.9 and 8.3 l/min, respectively. There was no significant difference in exacerbations or in side effects. CONCLUSION: There were no overall significant differences between the low dose steroid, low dose steroid with theophylline, and the high dose steroid groups. The greatest within-group improvement in evening peak flows was found after theophylline. A larger study may be necessary to show significant effects.